Usulan Perbaikan Proses Pencampuran Powder Jelly Dengan Metode Failure Mode and Effect Analysis (FMEA) Dan Pengurangan Waktu Proses di Pabrik Pangan - Heris Muhamar; Hery Hamdi Azwir (JIE Scientific Journal on Research and Application of Industrial System, 2019)
Food factory is a chemical trading and processing company for semi-finished food. One of the processed foods produced is jelly powder. The problems faced by food manufacturers are how to reduce the occurrence of product defects and the length of product mixing process that is 180 minutes for A-type 147 jelly. Proposed improvements are made by the Failure Mode and Effect Analysis (FMEA) method where defective products occur at most hardness and syneresis parameters and are caused by 4 elements namely method, environment, human, and material. In this proposed improvement, additional methods are carried out by reconsideration after the raw material is grinding (puree) because in this process additive raw materials which are free flowing will be reduced due to exposure to air, added temperature control devices in raw materials, training on raw materials, and search for new suppliers with the same specifications. At the reduction of processing time, the mixing time is 150 minutes, so the food factory can reduce the mixing time by 30 minutes.